Genomic CDKN2A/2B deletions in adult Ph+ ALL are adverse despite allogeneic stem cell transplantation - Pfeifer, Heike; Raum, Katharina Milena; Nowak, Verena; Obländer, Julia; Pressler, Jovita; Hofmann, Wolf-Karsten; Weiß, Christel; Nowak, Daniel (Blood, 2018)
Key Points. Genomic deletions of CDKN2A/2B are a new independent prognostic risk factor in adult Ph+ ALL.